2020
DOI: 10.3389/fphar.2020.00484
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxypropyl-β-Cyclodextrin Complexes of Styryllactones Enhance the Anti-Tumor Effect in SW1116 Cell Line

Abstract: Styryllactones, a class of compounds obtained from the genus Goniothalamus (Annonaceae), have demonstrated in vitro antitumor activity. However, the aqueous solubility of these compounds is poor. In this study, we identified the absolute configurations of the previously isolated compounds, which were first isolated in our laboratory, by single-crystal X-ray diffraction analysis using Cu Ka radiation. Subsequently, the antitumor activities of the compounds were evaluated by 3-(4,5dimethylthiazol-2-yl)-2,5-diphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…C-6 was assigned as R based on the analysis of the ECD spectrum of 7 (Figure S65), which was consistent with the spectrum of leiocarpin B. 16 This, combined with the NMR data (Table 4), led us to assign the absolute configuration of 7 as 6R,7R,8R,2′S and to name it 6R,7R,8R,2′S-goniolactone G (7).…”
Section: ■ Results and Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…C-6 was assigned as R based on the analysis of the ECD spectrum of 7 (Figure S65), which was consistent with the spectrum of leiocarpin B. 16 This, combined with the NMR data (Table 4), led us to assign the absolute configuration of 7 as 6R,7R,8R,2′S and to name it 6R,7R,8R,2′S-goniolactone G (7).…”
Section: ■ Results and Discussionsupporting
confidence: 65%
“…Bioassays of Human Colorectal Cancer Cells and Hepatocellular Carcinoma Cell Lines. 7 Different human colorectal cancer cells and hepatocellular carcinoma cell lines, including COLO205, LS513, SW620, HCCLM3, MHCC97H, HepG2, and HuH7, were obtained from Zhongshan Hospital, Fudan University. All cell lines were cultured in complete Dulbecco's modified Eagle's medium (DMEM) containing 10% fetal bovine serum (FBS), 100 U/mL penicillin, and 0.1% streptomycin.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, cell cytotoxicity and inclusion complex uptake studies revealed that HPβ-CD/PA NFs drug deliveries exhibited promising anti-cancer drug release and can be suggested for human colon cancer treatment. 66 According to the above characterizations, HPβ-CD/PA NFs inclusion complex was synthesized and showed much better chemical and biological properties. To our best knowledge, it is the first time to synthesis HPβ-CD/PA NFs inclusion complex and targeted modification was also carried out.
Figure 8.(a) Cell viability of PA, HPβ-CD, and the inclusion complex HPβ-CD/PA (20–100 μg/mL) on HCT-116 cells after 24 h. Data are presented as mean ± standard deviation ( n =3).
…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, only the 2D structure was proposed for cheliensisine; however, pinocembrin and its derivatives isolated from Goniothalamus sp. had been reported to have (2 S ) configurations. Therefore, the absolute structure of cheliensisine was presumed to be the same as that of aquiledine ( 6 ). The specific rotations of 9 and 10 were calculated to assign the absolute structure of isoaquiledine in a similar manner.…”
Section: Results and Discussionmentioning
confidence: 99%